The association of metabolic syndrome and its components with serum prostate-specific antigen levels. Issue 1 (January 2020) - Gao, Xiaoshuai; Bao, Ting; Yang, Hanwei; Lei, Yali; Jiang, Xianwen; Huang, Yan; Huang, Wenxia; Tang, Huairong
Abstract : Metabolic syndrome (MetS) can increase the risk of prostate cancer. Prostate-specific antigen (PSA) is the marker for prostate cancer puncture screening. The aim of our study was to investigate the association between MetS and its components with PSA levels. Data were obtained from 482 943 healthy men who underwent routine health check-ups from January 2010 to December 2017. We used linear regression analysis to evaluate the effects of MetS and its components on PSA levels. To explore the cumulative effect of MetS components, analysis of variance trend analysis was carried out. The PSA levels in the group with MetS were significantly lower than those without MetS ( P  =   0.001). In the multivariate regression model, age ( P  <   0.001) and hypertension ( P  <   0.001) were correlated positively with PSA levels; nevertheless, obesity ( P  <   0.001), hypertriglyceridemia ( P  <   0.001), hyperglycemia ( P  <   0.001), and low high-density lipoprotein cholesterol level ( P  <   0.001) had a negative correlation. In addition, after adjustment for age, increasing sums of positive MetS components were associated with a linear decrease in PSA levels ( P <0.001). In conclusion, MetS, obesity, hypertriglyceridemia, hyperglycemia, and low high-density lipoprotein cholesterol levels are associated with decreased PSA levels. For patients with PSA levels at the critical value of prostate puncture, the effect of these diseases in reducing PSA levels should be taken into account.